2013
DOI: 10.1016/j.pain.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in emotion-related cognitive processes in irritable bowel syndrome and healthy control subjects

Abstract: Background/Aims Greater responsiveness of emotional arousal circuits in relation to delivered visceral pain has been implicated as underlying central pain amplification in Irritable Bowel Syndrome (IBS), with females showing greater responses than males. Methods Functional MRI was used to measure neural responses to an emotion recognition paradigm, using faces expressing negative emotions (fear and anger). Sex and disease differences in the connectivity of affective and modulatory cortical circuits were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 80 publications
2
75
0
Order By: Relevance
“…[52] IBS patients exhibit hyperactivity in the amygdala and connected brain regions both at baseline and in response to visceral stimulation. [53,54] In some studies at least, sex and genetic differences have been identified in IBS-induced amygdala hyperactivity, and stronger effects are observed in males [55] and those with a particular polymorphism of the serotonin receptor gene, HTR3A. [56] Overall, amygdala hyperactivity seems to be related to chronic visceral hypersensitivity, pointing to another important link between the gut and the amygdala.…”
Section: Amygdala Regulates Affective Responses In Pain and Irritablementioning
confidence: 99%
“…[52] IBS patients exhibit hyperactivity in the amygdala and connected brain regions both at baseline and in response to visceral stimulation. [53,54] In some studies at least, sex and genetic differences have been identified in IBS-induced amygdala hyperactivity, and stronger effects are observed in males [55] and those with a particular polymorphism of the serotonin receptor gene, HTR3A. [56] Overall, amygdala hyperactivity seems to be related to chronic visceral hypersensitivity, pointing to another important link between the gut and the amygdala.…”
Section: Amygdala Regulates Affective Responses In Pain and Irritablementioning
confidence: 99%
“…Comparatively, only a few functional connectivity studies have examined the neural bases of sex-differences in emotion processing. Although the specific pathways differentiating women and men are yet to be identified, sex-differences have been observed in various fronto-limbic pathways (Labus et al, 2013;Moriguchi et al, 2014).These neurofunctional differences may reflect differences in emotion regulation or action preparation.Indeed, a recent neuroanatomical study found a positive correlation between emotion regulation and gray matter volume in the right dorsolateral prefrontal cortex in men,whereas in women there was a stronger positive relationship between emotion regulation and a gray matter volumein a clusterincluding the left hippocampus, the amygdala and the insula (Kong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the emotional response or valence can never be separated from the CNS processing of pain and visceral sensation. With respect to the affective-motivational component, the amygdala and hippocampus constitute the major network nodes in the emotional arousal network [14, 15], together with the involvement of the hypothalamus [16]. The MCC with its reciprocal connections with the lateral and medial DPFC and SMA mediates the motivational aspect of visceral sensation and response selection [17].…”
Section: Discussionmentioning
confidence: 99%